3D-CFD investigation into free convection flow above a heated horizontal cylinder: Comparisons with experimental data. (25th June 2017) - Lin, Kuang C.; Bhosale, Yashraj; Zhou Huang, Cun-Yan
Highlights: A 3D computational model is developed for free convection over a heated cylinder. Experimental PIV and Nu data are validated by the CFD model for the first time. A correlation between the boundary layer and flow mechanisms is revealed. Periodic swaying motion in all three dimensions is detected. A frequency of Nusselt number variations corresponds to the plume oscillation. Abstract: A 3-D computational fluid dynamics (CFD) model is proposed for the first time to predict the existing particle-image velocimetry (PIV) data and measured Nusselt numbers collected from the liquid flow above a heated horizontal cylinder. The simulation results are obtained in the free convective water flow around a heated horizontal cylinder with the top surface open to air in the Rayleigh number range from 10 5 to 5 × 10 6 and a Prandtl number of 5.98. The submersion depth of the cylinder top below the free water surface is normalized by the cylinder diameter at H / D = 6. Excellent agreements between the computed and measured similarity solutions for a Rayleigh number of 1.33 × 10 6 prove the capability of the computational model to simulate flow velocity, boundary layers and Nusselt numbers present in a vertical plane perpendicular to the cylinder axis at different circumferential locations. The computational results concerning the periodic swaying motion of the plume and its time of a sway period are found to be consistent with the experimental observations. Additionally, the computational analysis reveals the correlation among the near-cylinder flow features, boundary-layer thickness and plume formation region. We further analyze the correspondence between the swaying motion in a plane perpendicular to the cylinder axis and meandering structure coupled with U-shaped velocity profiles in the axial direction. Furthermore, the effect of Rayleigh number on the velocity fields and heat transfer characteristics has been identified. In the frequency spectrum analysis of the Nusselt number fluctuations, we have found the correlation between the oscillation frequency of the plume swaying and heat transfer characteristics.